2022
DOI: 10.1111/bjh.18190
|View full text |Cite
|
Sign up to set email alerts
|

The significance of mixed chimaerism and cell lineage chimaerism monitoring in paediatric patients post haematopoietic stem cell transplant

Abstract: Haematopoietic stem cell transplants (HSCTs) are carried out across the world to treat haematological and immunological diseases which would otherwise prove fatal. Certain diseases are predominantly encountered in paediatric patients, such severe primary immunodeficiencies (PID) and diseases of inborn errors of metabolism (IEM). Chimaerism testing for these disorders has different considerations compared to adult diseases. This review focuses on the importance of cell-lineagespecific chimaerism testing and exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 114 publications
0
4
0
Order By: Relevance
“…Chimerism is a dynamic process and ever-changing, and MC is responsible for allo-HSCT failure ( 21 ). The most appropriate chimerism analysis is based on disease and allo-HSCT type ( 22 ). However, there is a lack of comparative analysis of different chimerism of dynamic changes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chimerism is a dynamic process and ever-changing, and MC is responsible for allo-HSCT failure ( 21 ). The most appropriate chimerism analysis is based on disease and allo-HSCT type ( 22 ). However, there is a lack of comparative analysis of different chimerism of dynamic changes.…”
Section: Discussionmentioning
confidence: 99%
“…Through successive tests can be able to effectively identify high-risk relapse patients, which indicates close monitoring is extremely important ( 26 , 27 ). Donor cells need time to rebuild the hematopoietic system after allo-HSCT, so it is not advisable to assess the chimerism status after transplantation too early ( 22 ). In this study, the study was examined from 15 days after allo-HSCT, and the study’s duration was restricted to a 30-month follow-up period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Engraftment studies showed that the patient had 100% myeloid and whole blood engraftment confirming that the transplanted cells were what was detected in the patient. Erythroid engraftment can only be directly assessed by separating erythroid precursors from bone marrow samples (such as CD235a‐positive selection) [5]; however, bone marrow samples were not available for this patient. Myeloid engraftment has been described as a surrogate marker for erythroid engraftment [5], and given that the patient is fully engrafted in whole blood and myeloid without evidence of any low‐level mixed chimerism, it can be concluded that the patient's erythroid cell lineage is also fully engrafted.…”
Section: Introductionmentioning
confidence: 99%